Employer’s safety and health responsibility: with reference to selected workplace violations - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2019)
Any violation of the employer’s rules on safety and health is considered a misconduct that would entail disciplinary action. The following acts or conducts of an employee which may compromise the health and safety of others at the workplace are discussed: (a) threats, intimidation and violence; (b) sexual harassment; (c) smoking at restricted or prohibited areas; (c) drugs and alcohol abuse; and (d) sleeping while on duty. Such occurrence in the workplace is considered rampant and hence, the consequences ensuing from violation thereto is discussed in the context of employer’s workplace safety and health obligation.